A return to lived experiencers themselves: Participatory action research of and by psychosocial clubhouse members - Vescey, Lester; Yoon, Jennifer; Rice, Kevin, Members of PARCO Group; Davidson, Larry; Desai, Miraj (Frontiers in Psychology, 2023)
Within the history of psychology and phenomenology, people with lived experience of mental illness have often served as participants in research, but far less as co-researchers themselves. There is now a growing movement focused on “participatory” research, where people with lived experience directly contribute to various stages of the research process. This practice helps enhance the relevance of research for stakeholders’ lives and worldly contexts. This article presents such a qualitative, participatory research study, conducted by members of a large psychosocial rehabilitation clubhouse, and informed by phenomenological research principles. The study was intended to understand and improve the experience of the clubhouse and the clubhouse model for its members with severe mental illness. An innovation of the project was the sheer extent of stakeholder involvement, i.e., in designing and conducting the study, and co-writing this research report. Overall, study findings place emphasis on the theme of action in members’ experiences—both with respect to how action, agency, and meaningful activity were key drivers of meaning and recovery for people facing severe mental illness, and with respect to the key component of the research process itself (i.e., participatory action research). These action-oriented themes serve as a clear counter to the historical view of people with mental illness as merely passive experiencers of symptoms and passive recipients of mental health care. The article then details the major findings of the ensuing qualitative study on clubhouse experiences. First, we examine how members with mental illness experienced the clubhouse as a “new hope” and “the place for me,” to counteract their experience of inactivity, stigma, depression, and hopelessness prior to that point. Second, findings showed how such a hospitable, non-hospital setting did not hold a uniform meaning across time for members with mental illness. Third, findings portrayed members’ need for, and pursuit of, transformation within the clubhouse space itself to provide more opportunities for meaningful work rather than what they viewed as merely busy-work. These themes, together, emphasize the centrality of action, agency, and meaningful activity with respect to the lives and recovery processes of people with mental illness.